(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of the Cooperative Learning model assisted by the quizwhizzer media in improving students’ learning outcomes in English subjects for Grade X at MA Subulul Huda Darma. The study employs a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The sample consisted of two classes: the experimental class, which used the Cooperative Learning model with Quizwhizzer, and the control class, which used conventional methods. Data collection was conducted through pretest and posttest, analyzed using normality test, homogeneity test, and an Independent Sample T-Test. The hypothesis test results showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating a significant difference in learning outcomes between the two classes. Thus, the use of the Cooperative Learning model assisted by Quizwhizzer media proved effective in improving students’ learning outcomes. This model is capable of creating an interactive, enjoyable learning environment and increasing students’ active engagement.